P229 Integrated analysis of dermal blister fluid proteomics and skin biopsy transcriptomics gives new insight into pathogenesis of systemic sclerosis. (23rd April 2022) - Clark, Kristina E. N; Csomor, Eszter; Campochiaro, Corrado; Teo, Yee Voan; Freudenberg, Johannes; Nevin, Katherine; Morse, Mary A; Ong, Voon H; Derrett-Smith, Emma; Wisniacki, Nicolas; Flint, Shaun M; Denton, Christopher P
Abstract: Background/Aims: Suction blister fluid (BF) provides a unique opportunity to analyse the dermal microenvironment of SSc. We utilised an integrated approach to analyse proteomic data from dermal interstitial fluid and genome-wide transcriptomic data from skin biopsies from early dcSSc and healthy controls (HC). Interpreting differential protein expression in the context of RNA sequencing (RNAseq) provides unique insight into potential mediators and pathways relevant to SSc. Methods: The BIOPSY cohort recruited 21 early dcSSc patients with mean skin score (MRSS) of 21 (sd 11) and 16 HCs. Forearm skin BF was obtained using the dermal suction blister method and assayed using the Olink platform (www.olink.com ) (1192 proteins). Simultaneous 4mm punch biopsies were taken from all subjects, for genome-wide transcriptomic profiling by RNAseq. Integrated analysis of clinical characteristics, gene and protein expression data was conducted using WGCNA and clusterProfiler in R. This method clusters individual analytes into modules sharing similar expression patterns. Each module has been arbitrarily assigned as a colour. Results: WGCNA identified 6 modules in BF, and 30 modules from skin. Two BF modules and three in the skin positively correlated with each other, and all of them correlated with a diagnosis of early dcSSc. The magenta module in the skin (385 genes) and blue module (450 proteins) in BF had the strongest correlation (r = 0.74, p < 0.001 and r = 0.6, p < 0.001 respectively). Interrogating each module, key biological processes consistent with current concepts of SSc pathogenesis were identified, and skin and blister modules largely seemed to complement each other. Magenta module processes focused on angiogenesis, extracellular matrix (ECM) structure, and endothelial cell proliferation, with the highest fold change in COMP (FC = 5.06, p<0.001), COL4A4 (FC = 3.86, p<0.001), COL11A1 (FC = 3.46, p<0.001) having the highest fold change compared to HC. The red module from the skin transcriptomics consisted of genes relating to immune activation, whereas the interferon signature was predominantly seen in the genes of the pink module. Within BF proteomics, the blue module consisted of proteins centred around ECM organisation, cell adhesion, and response to TNF, with upregulation of SFRP1 (FC = 4.88, p = 0.013), TNC(FC = 4.81, p=0.0018) and KLK4 (FC = 7.17, p<0.001) in early dcSSc. Whereas metabolic processes were the centre of the turquoise module. Significant Hallmark pathways were compared between all five modules in each tissue modality. Notably, some pathways were upregulated in both skin gene expression and blister fluid modules including NFKB signalling, allograft rejection, and interferon gamma response. Significantly activated pathways in skin gene but not the blister protein modules include G2M checkpoint, p53 pathway, and xenobiotic metabolism. Conversely, protein secretion, unfolded protein response and mitotic spindle pathways were significantly increased only in the blister modules. Conclusion: Simultaneous high dimensional analysis of skin gene and protein expression gives new insight into the molecular pathology of SSc. This provides a potential platform for developing a novel composite biomarker for skin. Disclosure: K.E.N. Clark: None. E. Csomor: Corporate appointments; employee of GSK. C. Campochiaro: None. Y. Teo: Corporate appointments; employee of GSK. J. Freudenberg: Corporate appointments; employee of GSK. K. Nevin: Corporate appointments; employee of GSK. M.A. Morse: Corporate appointments; employee of GSK. V.H. Ong: None. E. Derrett-Smith: None. N. Wisniacki: Corporate appointments; employee of GSK. S.M. Flint: Corporate appointments; employee of GSK. C.P. Denton: None.